Sisymbrium linifolium and Sisymbriopsis schugnana (Brassicaceae), two new records from Xinjiang, China - Hongliang Chen; Ihsan A. Al-Shehbaz; Jipei Yue; Hang Sun (PhytoKeys, 2019)
Sisymbrium linifolium and Sisymbriopsis schugnana, previously confined to western North America and Tajikistan, respectively, were discovered in Xinjiang during a recent field trip to this autonomous region of China. The identity of these two species was subsequently confirmed by extensive morphological and molecular studies. The biogeographical significance of these new floristic records is briefly addressed.